Comparative study of Lipid Profile in Dianova chooranam and Mathumega chooranam on Type -II Diabetes mellitus Patients - Sritharan, A.; Sritharan, G. (National Ayurvedha Research, 2012)
Under diabetic conditions not only glucose level, lipid level also can be altered. Hence, different compounds are being used in the treatment of elevated lipid profile. A study was carried out to investigate the anti-hyperlipidaemic effect of Dianova, a poly herbal Sidda formulation with Mathumega choornam. The churanam (powder) of Dianova consists of 6 herbs namely Gymnema sylvestre, Eugenia jambolana, Salasia riticulata, Curcuma longa, Terminalia chebula and Phyllanthus embilica. Dried ingredients were ground and packaged in airtight containers. As all the six herbs were reported to have antidiabetic effect and the clinical efficacy of "Dianova" was assessed. The patients with Diabetes mellitus who attended a private Siddhha hospital at Jaffna from September 2009 to January 2010 were taken to the present study after getting an approval of the Ethical Committee, University of Jaffna. A total of 20 patients of either sex, aged between 55-65, who consented to give information were included in the study.
Keywords: Diabetes mellitus; Dianova; Siddha formulation; Antihyperlipidaemic poly herbal.